Those 45 Minutes Changed My Life: The Meeting of Sigmund Freud and Margarethe Lutz. Issue 3 (1st September 2016) - Slavin, Jonathan H.; Rahmani, Miki
Abstract : The editors of this series of papers introduce the account of Margarethe Lutz, a patient who saw Sigmund Freud for one session and spoke of it 70 years later. It was an experience, she said, that "changed her life." The editors note that there are few, if any, accounts of treatment with Freud that illustrate in such detail the unfolding of an individual session. The editors asked the authors of the seven papers in this issue to address the question of what, in this single session, may have led to its life-changing impact and the implications this may have for the way contemporary psychoanalysts and psychotherapists think about their work.